222k views
1 vote
Need the answer please.

Need the answer please.-example-1

2 Answers

1 vote

Answer:

The correct answer is option A. ab

Explanation:

Points to remember

Identities

Xᵃ * Xᵇ = X⁽ᵃ ⁺ ᵇ⁾

X⁻ᵃ = 1/Xᵃ

Xᵃ/Xᵇ = X⁽ᵃ ⁻ ᵇ⁾

To find the correct answer

It is given that,

a³b²/a²b

By using above identities we can write,

a³b²/a²b = a⁽³ ⁻ ²⁾b⁽² ⁻ ¹⁾

= a¹b¹ = ab

Therefore the answer is ab

The correct option is option A. ab

User Hai Feng Kao
by
5.4k points
4 votes

Answer: Option A.

Explanation:

You need to remember the Quotient property of powers, which states the following:


(p^m)/(p^n)=p^((m-n))

Then, given the expression
(a^3b^2)/(a^2b), you need to apply this property to simplify this expression.

Therefore, you get:


=a^((3-2))b^((2-1))\\\\=a^1b^1\\\\=ab

As you can observe, this matches with the option A.

User Sago
by
5.3k points